2016
DOI: 10.1007/s11011-016-9807-0
|View full text |Cite
|
Sign up to set email alerts
|

Increase of kisspeptin-positive cells in the hypothalamus of a rat model of polycystic ovary syndrome

Abstract: Kisspeptin, a hypothalamic neuropeptide, is expressed in the arcuate nucleus (ARC) that is considered as the center of the gonadotropin-releasing hormone (GnRH)-pulse generator. We hypothesized that kisspeptin expressed in the ARC is implicated in the disturbance of the hypothalamus-pituitary-ovary axis observed in polycystic ovary syndrome (PCOS). To test this hypothesis, we evaluated the hormonal profiles, luteinizing hormone (LH) pulse, and ARC kisspeptin immunoreactivity in a PCOS rat model using the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…P 4 treatment increased Dyn concentrations and decreased LH pulse frequency in cerebrospinal fluid and restored preprodynorphin mRNA expression in the hypothalamus in an ovariectomized ewe [40], suggesting that Dyn in the KNDy neuron inhibited kisspeptin release and GnRH/ LH pulse frequency via P-mediated negative feedback. Recently, Kondo et al reported that a PCOS model rat induced by the anti-progestin RU486 showed increased kisspeptin immunoreactivity in ARC, which might be involved in the pathophysiology of PCOS women [41]. Their finding is similar to our finding, even though we used a different induction method, suggesting the importance of enhanced KNDy neuron activity in PCOS pathophysiology.…”
Section: Discussionsupporting
confidence: 89%
“…P 4 treatment increased Dyn concentrations and decreased LH pulse frequency in cerebrospinal fluid and restored preprodynorphin mRNA expression in the hypothalamus in an ovariectomized ewe [40], suggesting that Dyn in the KNDy neuron inhibited kisspeptin release and GnRH/ LH pulse frequency via P-mediated negative feedback. Recently, Kondo et al reported that a PCOS model rat induced by the anti-progestin RU486 showed increased kisspeptin immunoreactivity in ARC, which might be involved in the pathophysiology of PCOS women [41]. Their finding is similar to our finding, even though we used a different induction method, suggesting the importance of enhanced KNDy neuron activity in PCOS pathophysiology.…”
Section: Discussionsupporting
confidence: 89%
“…The ovaries of RU486‐treated rats showed follicular growth arrest and a higher rate of follicular atresia . The numbers of preantral and small antral follicles and atretic cyst‐like follicles—but not of large antral follicles—were also increased relative to untreated rats …”
Section: Progesterone Receptor Antagonist‐induced Modelsmentioning
confidence: 95%
“…Evidence from clinical studies indicates that RU486 suppresses follicle development, ovulation, and CL formation by disrupting the negative feedback of P4 to the hypothalamus. Accordingly, RU486 has been used to generate rat models of PCOS by administering 2 mg RU486/100 g body weight to adult rats for 1‐2 weeks …”
Section: Progesterone Receptor Antagonist‐induced Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they demonstrated that the enhanced neural cells in PCOS rats might contribute to the hypersecretion of LH. Similarly, Kondo et al [28] who studied ARC kisspeptin immune reactivity by using antiprogestin R4486 found that besides the increase in the LH level, there was also an increase in the number of kisspeptin-positive cells in the hypothalamus. On the contrary, Marcondes et al [29,30] did not agree with this.…”
Section: Discussionmentioning
confidence: 84%